Chronicle of the Turkish financial crises of 2000-2001 - Van Rijckeghem, Caroline; Üçer, Murat (Boğaziçi Üniversitesi, 2005)
The Turkish crisis of November 2000, while not entirely unexpected, caught the world by surprise. It was only 10 months into an IMF supported disinflation program, which was working generally well despite several shortcomings, and the political backing for the program was stronger than anything Turkey could hope for. But the crisis hit violently, with interest rates breaking world records, and much earlier than experienced in other "exchange rate-based" stabilization programs. The crises cost Turkey the most severe contraction of its modern history since the 1940s.Sayfa Sayisi: 195Dili: IngilizceYayinevi: Bogazici Universitesi Yayinevi